A solution-processed near-infrared polymer: PbS quantum dot photodetectors. Issue 55 (11th July 2017) - Xu, Wenzhan; Peng, Hui; Zhu, Tao; Yi, Chao; Liu, Lei; Gong, Xiong
Abstract : Operating at room temperature, a solution-processed photodetector with near infrared sensitivity would be a significant advancement towards industrial and scientific applications. Abstract : Operating at room temperature, a solution-processed photodetector with near infrared sensitivity would be a significant advancement towards industrial and scientific applications. Polymer-inorganic quantum dot (QD) composites are attractive due to combination of the merits of polymeric and inorganic semiconductors in novel electronic and photonic systems. Inorganic QDs are highly suitable as infrared absorbers, and polymer bulk heterojunctions are attractive as solution-processable diodes. Herein, we demonstrated a photodetector with a spectral response ranging from 300 nm to 1600 nm using a bulk heterojunction composite of a wide bandgap conjugated polymer with narrow bandgap PbS QDs. Operating at room temperature, the solution-processed photodetectors exhibit a detectivity greater than 10 10 cm Hz 1/2 W −1 and an external quantum efficiency of over 80% in the visible region and 10% in the infrared region. All these device performances are comparable to those of their inorganic counterparts. Thus, our results demonstrate a simple way to fabricate uncooled solution-processed broadband photodetectors.